2020
DOI: 10.4014/jmb.1911.11068
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Linderone Suppresses TPA-Stimulated IL-8 and MMP-9 Expression Via the ERK/STAT3 Pathway in MCF-7 Breast Cancer Cells

Abstract: Methyl linderone (ML), a cyclo-pentenedione, was isolated from the fruit of Lindera erythrocarpa Makino (family Lauraceae). This plant has well-known anti-inflammatory effects; however, the anti-cancer effects of ML have not yet been reported. Thus, in the present study we investigated the effects of ML on the metastasis of human breast cancer cells. We used 12- O-tetradecanoyl phorbol-13-acetate (TPA)-stimulated MCF-7 cells as the cell model to study the effects of ML on invasion and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Our results showed that TMEM9 increased the phosphorylation levels of MEK, ERK, and STAT3. Previous studies have shown that STAT3 is a downstream target of the ERK signaling pathway in various tumors [37][38][39][40]. Consistent with previous findings, we also found that U0126 treatment reduced protein levels of p-STAT3 in TMEM9-overexpressing LUAD cells.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that TMEM9 increased the phosphorylation levels of MEK, ERK, and STAT3. Previous studies have shown that STAT3 is a downstream target of the ERK signaling pathway in various tumors [37][38][39][40]. Consistent with previous findings, we also found that U0126 treatment reduced protein levels of p-STAT3 in TMEM9-overexpressing LUAD cells.…”
Section: Discussionsupporting
confidence: 92%
“…Miconazole suppresses the expression of HIF1α through post-transcriptional regulation in glioma and breast cancer-derived cell lines; this was attributed to the inhibition of mammalian target of rapamycin (mTOR) and regulation of protein synthesis via induction of the phosphorylation of eIF2α, a downstream target of mTOR (Park et al, 2014). In lung cancer cells, miconazole suppresses pSTAT3 Y705 and inhibits the expression of target genes involved in growth, migration, and invasion (Yoon et al, 2020). Further investigations are needed to determine whether miconazole suppresses the 27OHCholinduced cellular responses by acting on the R-Ras, mTOR, or STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl linderone (ML) ( Figure 4 ) is a cyclo-pentenedione isolated from the fruits of Lindera erythrocarpa (family Lauraceae). Yoon et al [ 195 ] identified that treatment with ML inhibits breast cancer. After performing a cell viability assay, they found that 10 μM is the nontoxic dose of ML.…”
Section: Small-molecule Natural Products As Ras Inhibitorsmentioning
confidence: 99%